Numerical Simulation of Impact Behaviour of Structures with Internal Pressurization for Crash-Adaptive Concept - Miguel NOVERSA; Nuno PEIXINHO (Engineering Transactions, 2013)
This study presents an alternative approach for the absorption of impact energy that uses the internal pressurization of structures in the framework of a crash-adaptive response. Numerical simulations were conducted on the axial impact of thin-walled tubular structures with circular cross-section that serves as an approximation to a front crash box of a motor vehicle. The main objective of this work consists in studying the effect of internal pressurization of tubular structures in a crashworthiness application, as well as the possibility to obtain a reduction in wall thickness thus improving weight efficiency. A numerical study is presented for an internal pressure of 20 bar and tubular structures of circular section and 1.14 mm thickness. Numerical simulations were performed by making use of the LS-DYNA explicit dynamics software, while considering for the material a stainless steel alloy that is a material with interest for crashworthiness applications and manufacturing requisites due to its balance between strength, ductility, and energy absorption. The results obtained allow the conclusion, that with respect to internal pressurization it is feasible to reduce the wall thickness and have an impact resistance identical to the original while improving overall efficiency.